2011
DOI: 10.1108/09540911111099686
|View full text |Cite
|
Sign up to set email alerts
|

Thermal fatigue endurance of Sn3Ag0.5Cu0.5In0.05Ni and Sn2.5Ag0.8Cu0.5Sb solders in composite solder joints of LTCC/PWB assemblies

Abstract: Purpose -The purpose of this paper is to investigate the thermal fatigue endurance of two lead-free solders used in composite solder joints consisting of plastic core solder balls (PCSB) and different solder materials, in order to assess their feasibility in low-temperature cofired ceramic (LTCC)/printed wiring board (PWB) assemblies. Design/methodology/approach -The characteristic lifetime of these joints was determined in a thermal cycling test (TCT) over a temperature range of 240-1258C. Their failure mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Voids themselves present an easy fracture path for a propagating crack, but they also concentrate stresses in their vicinity. This results in more severe strain and the formation of a recrystallized area [13,14]. This behavior was also observed in SnAg joints, as shown in Figure 10.…”
Section: B Metallographic Investigationsupporting
confidence: 55%
“…Voids themselves present an easy fracture path for a propagating crack, but they also concentrate stresses in their vicinity. This results in more severe strain and the formation of a recrystallized area [13,14]. This behavior was also observed in SnAg joints, as shown in Figure 10.…”
Section: B Metallographic Investigationsupporting
confidence: 55%
“…The primary failure of the joints of assembly B was located within the solder matrix, as shown in Figure 8(b). The observations of FE-SEM analysis (Figures 10 and 11) proved that a mixture of transgranular (fatigue) and intergranular (creep) failures formed in the SAC387 and SAC-InNi joints at the low-temperature extreme, similar to the joints of AgPtmetallized modules (Nousiainen et al, 2007b(Nousiainen et al, , 2010. Considering the width of the striations on the fracture surface, the growth rate of the transgranular (fatigue) crack in SAC-InNi was identical with the similar joint of AgPtmetallized modules (Nousiainen et al, 2010), whereas the SAC387 joints showed better fatigue endurance compared with Sn4Ag0.5Cu alloy (Nousiainen et al, 2007b).…”
Section: Failure Mechanisms Of the Test Joint Configurationsmentioning
confidence: 79%
“…The observations of FE-SEM analysis (Figures 10 and 11) proved that a mixture of transgranular (fatigue) and intergranular (creep) failures formed in the SAC387 and SAC-InNi joints at the low-temperature extreme, similar to the joints of AgPtmetallized modules (Nousiainen et al, 2007b(Nousiainen et al, , 2010. Considering the width of the striations on the fracture surface, the growth rate of the transgranular (fatigue) crack in SAC-InNi was identical with the similar joint of AgPtmetallized modules (Nousiainen et al, 2010), whereas the SAC387 joints showed better fatigue endurance compared with Sn4Ag0.5Cu alloy (Nousiainen et al, 2007b). The SEM and FE-SEM analyses (Figures 8(b), 10 and 11) also confirmed that intergranular (creep) failure was the dominant mechanism at the inner edge of the joint, not separation between the IMC layer and the lead-free solder matrix.…”
Section: Failure Mechanisms Of the Test Joint Configurationsmentioning
confidence: 79%
See 1 more Smart Citation